AB0998 Evaluation of The Effectiveness of Joint Status Self-Assessment by Patients with Rheumatoid Arthritis. (15th July 2016) - Yurova, E.; Lygina, E.; Yakushin, S.; Bagirova, G.; Vorobyev, A.
Abstract : Objectives: The cooperation in the "doctor-patient" pair is necessary to implement the TREAT TO TARGET conception in the management of rheumatoid arthritis (RA). For greater adherence to treatment, self–control of the disease activity is important for a patient. We have created an original method of training RA patients to self-assess the count of swollen and tender joints correctly. The objective of the research was to study the effectiveness of the method of training patients to self-assess the RA activity. Methods: The study included 96 patients with the definite diagnosis of RA, according to the ACR/EULAR 2010 diagnostic criteria (88 females; 8 males, mean age 58, 1 (51, 0; 65, 0), the median duration of RA was 8, 3 (2, 0; 11, 5). During the first visit patients were trained using the original method of Disease Activity Self-Assessment (the physician demonstrated the technique of self-assessment of swollen and tender joints and provided the patient with printed guidelines and photos). During the second and third visits with one-month interval, there was an independent control of swollen and tender joint count by a physician and a patient. Statistical significance was analyzed using the McNemar's test. Results: Absolute coincidence of the number of tender joints as assessed in parallel by a physician and a patient was observed in 35 cases during the second visit and in 62 (p=0, 01) cases during the third visit. Absolute coincidence of the number of swollen joints as assessed in parallel by a physician and a patient was observed in 43 cases during the second visit and in 65 (p=0, 01) cases during the third visit. Conclusions: Our original method of Disease Activity Self-Assessment allows training most patients with RA to assess swollen and tender joints. This is important for self-control of the diseases activity and allows a patent to visit a physician for timely therapy correction. Disclosure of Interest: None declared